An exercise-associated gut microbiota signature enhances endurance performance: A study combining a human cohort and a mice FMT model - Xiongbao Zhang; Yating Fu; Jiahui Chen; Hao Shen; Yumeng Du; Jun Wu; Hongjing Lai; Yu Liu; Jingbo Chen; Xiaomei Hou; Wenjun Chang; Xuefei Hu (PLoS ONE, 2026)
Background The gut microbiota is closely related to exercise, but the interrelationship between the two remains elusive. In this study, we aimed to explore differences in the gut microbiota between young adults with exercise and sedentary lifestyles. In addition, we evaluated the effects of gut microbiota from these different lifestyle populations on endurance exercise capacity. Methods The exercise status and nutritional characteristics of young adults were evaluated by PARS-3 and food frequency questionnaires. The gut microbiota of young adults from exercise and sedentary lifestyle groups was analyzed by 16S rRNA analysis. Subsequently, we performed fecal bacteria transplantation (FMT) from the human donors into mice and evaluated the effects on their endurance exercise capacity. Results The exercise group exhibited significantly higher gut microbiota diversity compared to the sedentary group. Several beneficial bacteria, including Veillonella, Faecalibacterium, and Bacteroides, were enriched in the exercise group. The FMT experiment confirmed that mice receiving microbiota from the exercise group showed significantly improved endurance exercise capacity. Conclusion Young people who exercise regularly possess a more diverse gut microbiota enriched with beneficial bacteria. This exercise-associated microbiota has the potential to directly improve exercise capacity.